Experimental and theoretical investigations of adsorption of fexofenadine at mild steel/hydrochloric acid interface as corrosion inhibitor - Ahamad I.; Prasad R.; Quraishi M.A. (My University, 2025)
The present study examines the effect of fexofenadine, an antihistamine drug, on corrosion inhibition of mild steel in molar hydrochloric acid solution using different techniques under the influence of various experimental conditions. Results revealed that fexofenadine is an effective inhibitor and percent inhibition efficiency increased with its concentration; reaching a maximum value of 97% at a concentration of 3.0×10 -4∈M. Fourier-transform infrared spectroscopy (FTIR) observations of steel surface confirmed the protective role of the studied drug. Polarization studies showed that fexofenadine is a mixed-type inhibitor. The adsorption of the inhibitor on mild steel surface obeyed the Langmuir adsorption isotherm with free energy of adsorption (ΔG° ads) of -40 kJ mol -1. Energy gaps for the interactions between mild steel surface and fexofenadine molecule were found to be close to each other showing that fexofenadine has the capacity to behave as both electron donor and electron acceptor. The results obtained from the different corrosion evaluation techniques are in good agreement. © 2010 Springer-Verlag.